Strategi Menuju Pariwisata Bali yang Berkualitas - I Gusti Bagus Rai Utama (Jurnal Kajian Bali (Journal of Bali Studies), 2013)
AbstractThe nature and culture of Bali with all their manifestationshave yet to be able to attract tourists of high quality, eventhough the Balinese culture is undoubtedly popular inthe international tourism arena. This article offers qualitytourism management strategies in order to realize tourists’satisfaction, which in turn is hoped to increase the visitof quality and loyal tourists in the future. This studyutilizes desk research method with online data collectionand information gathering technique, using secondarysources and other published scientific sources. Analyticaltechniques utilized include quantitative and qualitativedescriptive analysis, and comparative analysis of previousresearch and scientific publications related to the economicand business dimensions of tourism. This researchrecommends that the implementation of quality tourismmanagement for Bali is of urgent importance because Bali’sdevelopment has been relying on the tourism sector. Thereare five dimensions of quality offered to Bali’s tourismoperators, ordered based on the important values fortourism customers: (1) tangible proof, (2) reliability, (3)responsiveness, (4) assurance, (5) empathy, which includesthe ease of building relationships, good communication,attentiveness, and understanding the needs of customerswhere the hospitality and politeness of the Balinese people is a form of empathy that is considered to be fading andneeds to be improved.